Electrolyte disorders during vancomycin treatment in hospitalized patients at hematology-oncology wards of Namazi hospital in Shiraz - Iman Karimzadeh; Ghazaleh Haghighati; Mani Ramzi; Mohammad Mahdi Sagheb; Kamiar Zomorodian (Shiraz University of Medical Sciences, 2016)
Increased serum creatinine level and decreased glomerular filtration rate are the major features of vancomycin nephrotoxicity. Electrolyte disorders of this agent have not been considered in relevant clinical studies so far. The aim of the present study was to determine potassium and magnesium disorders in patients with hematologic and oncologic diseases under vancomycin treatment. A cross-sectional, observational study was performed during 9 months at three hematology-oncology wards of Namazi hospital in Shiraz. Patients > 18 years with no documented history of acute kidney injury or chronic kidney disease planned to receive vancomycin for at least 1 week were recruited. Urine samples for determining creatinine, potassium, and magnesium levels were collected at days 0, 3, 5, 7, 10, and 14 of treatment. Hypokalemia and hypomagnesemia was defined as serum potassium and magnesium level below 3 mEq/L and 1.2 mEq/L, respectively. Two-fifth (40.38%) of the study population developed hypokalemia during 2 to 3 days after initiating vancomycin. Hypomagnesemia was detected in 5.77% of vancomycin recipients with the time onset of 7.67 ± 3.21 days. The mean ± standard deviation of potassium supplement was significantly higher in patients with than those without hypokalemia (P = 0.006). No case of renal potassium and magnesium wasting was identified. Amphotericin b co-administration significantly associated with hypokalemia during vancomycin treatment (odds ratio = 0.164 [95% confidence interval = 0.041-0.647], P = 0.01). In contrast to hypomagnesemia, hypokalemia occurred commonly during the first days of vancomycin treatment. However, the real casual relationship, mechanism, and clinical outcome of these electrolyte disorders in vancomycin recipients remain unclear.